Synthetic strategies for new vanadium oxyfluorides containing novel building blocks: structures of V(iv) and V(v) containing Sr4V3O5F13, Pb7V4O8F18, Pb2VO2F5, and Pb2VOF6. Issue 44 (3rd September 2015) - Yeon, Jeongho; Felder, Justin B.; Smith, Mark D.; Morrison, Gregory; zur Loye, Hans-Conrad
Abstract : Four novel vanadium oxyfluorides (VOFs) featuring new crystallographic building blocks were crystallized via a mild hydrothermal route. Abstract : Four new vanadium oxyfluorides (VOFs), Sr4 V3 O5 F13 (1 ), Pb7 V4 O8 F18 (2 ), Pb2 VO2 F5 (3 ), and Pb2 VOF6 (4 ), have been synthesized under mild hydrothermal conditions. The choice of starting reagents, AF2 or A(CH3 CO2 )2 · x H2 O (A = Pb, alkaline earth), determined the oxidation states of vanadium in the final products. The reaction of V2 O5 with AF2 leads, consistently, to the formation of V(v ) compounds, while the use of A(CH3 CO2 )2 · x H2 O results in V(iv ) containing compounds, suggesting that the acetate species behaves as an effective mild reducing agent. The crystal structures, characterized by single crystal X-ray diffraction, revealed that the compounds exhibit various anionic VOF building blocks, including dimeric and trinuclear units, as well as one-dimensional chains. All compounds contain fluorine atoms that are not bonded to the vanadium atoms, which are located between two-dimensional layers consisting of corner- or edge-shared FA3 or FA4 polyhedra that separate the vanadium containing building blocks. The magnetic susceptibility data for4 were measured as a function of temperature, yielding an effective magnetic moment of 1.72 μB that confirms the presence of V(iv ). UV-vis reflectance and thermal properties were also characterized.